Forest Product Marketing Strategies for MSMEs’ Business Sustainability in Central Kalimantan - Yuli Sintha Asi; Yulia Yulia; Mochamad Ramza Rapier Gussa; Indah Purnama Sari Mardjuni; Bambang Nurakhim (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the effect of social media marketing and offline marketing on the business sustainability of MSMEs in Central Kalimantan, as well as to examine the moderating role of MSMEs partnerships in strengthening these relationships. A quantitative approach was employed using hypothesis testing through regression and moderation analysis. The results show that social media marketing has a significant and positive effect on business sustainability (sig. 0.001), and offline marketing also has a significant and positive effect (sig. 0.000). Furthermore, MSMEs partnerships significantly moderate the relationship between social media marketing and business sustainability (Z = 3.12; sig. 0.0018), as well as the relationship between offline marketing and business sustainability (Z = 8.542; sig. 0.0018). In addition, social media marketing and offline marketing simultaneously have a significant effect on business sustainability (sig. 0.000). These findings indicate that an integrated marketing strategy, supported by strong partnerships, is essential for enhancing the sustainability of MSMEs in Central Kalimantan.